An accounting firm perspective of offshoring - Caratti, Silvia; Perrin, Brian; Scully, Glennda (2016)
Offshoring is increasingly being adopted by professional accounting firms of all sizes and has become a component of the larger Business Process Outsourcing (“BPO”) industry. The traditionally conservative accounting profession operates in an environment subject to an intense and dynamic regulatory oversight. There is increasing competition and a pressure to reduce costs and manage staffing shortages faced by the profession. Offshoring presents itself as a solution to these pressures and as such is a key motivator for adopting offshoring. This suggests that offshoring in accounting firms is worthy of being examined in its own right. Whilst offshoring generally has been the subject of much research, the use of offshoring in accounting firms, and in particular, research on the human resources aspect of offshoring for the domestic firm is scarce. This paper attempts to fill this void by investigating how the unique features of accounting firms apply to the general offshoring research through a rich case study approach. It demonstrates that “buy in” and human resourcing issues are important in ensuring the success of offshoring in accounting firms. This research in progress also examines the different offshoring ownership models adopted by accounting firms. Importantly, this paper introduces different interaction frameworks that firms can adopt, aiming to develop a model for firms to help them decide which is the most appropriate model and framework for them. In addition, this paper looks at the impact offshoring has on both the recruitment and development of domestic graduates in primarily Australian accounting firms and seeks to provide guidelines to assist firms in this area.